Designing a Novel Hybrid Material: Hydroxyl Iron (III) – Bentonite, Kaolinte Composites for Enhanced Phenol Removal from Wastewater: A Comparative Study - O, Egah G.; R, Sha’Ato; J, Ewenifa O.; U, Itodo A. (Darul Yasin Al Sys, 2024)
sources. This study examines Hydroxyiron (III) bentonite (HBC) and kaolin (HKC) composites for phenol removal from aqueous solutions (5–25 mg/L). The composites, produced by mixing bentonite and kaolin with Hydroxyiron (III) in a 3:1 ratio and calcined at 600°C for 1 hour, were tested at pH 2-11 and 25°C, with adsorbent dosages from 0.5 to 2.5 g in 50 mL solutions. Adsorption thermodynamics were developed for 1 hour, and kinetics experiments were performed at 25°C with a range of 10-60 minutes. Adsorption capacity increased with time, temperature, and concentration. HBC and HKC had pH values of 7.20 and 7.37, pHzpc of 10.10 and 11.00, conductivities of 1.657 and 1.763 μS/cm, bulky densities of 1.214 and 1.185 g/cm³, and attrition rates of 27.21% and 27.91%, respectively. XRF, FTIR, and SEM analyses confirmed hydroxyl group presence, indicating hydrogen bonding with phenol. The Blanchard pseudo-second order model best described HBC (R² = 0.906), and the pseudo-first order model best described HKC (R² = 0.957). Data fit the Langmuir model, indicating monolayer adsorption. Positive enthalpy, entropy, and Gibbs free energy values showed endothermic and non-spontaneous adsorption, with physisorption dominating chemisorption. Maximum adsorption efficiencies were 79.952% for HBC and 75.600% for HKC at 60 minutes, suggesting HBC is a more effective adsorbent. These results indicate that HBC and HKC can be used to remove organic pollutants from wastewater.